МЕТОДИКА ОБУЧЕНИЯ ОБУЧАЮЩИХСЯ ПО МИНИ- ФУТБОЛУ - Эшов Д.Н. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Education and training should be viewed as a unified, specially organized, long-term pedagogical process. There is no sharp boundary between them, since while teaching, we simultaneously train, and while training, we teach.